Layanan Bimbingan Kelompok Dengan Teknik Modeling Untuk Mengurangi Inferiority Siswa - Enggarini Pawestry, Audrey; Trisnowati, Eli; Maulana, Riki (Jurnal Bimbingan dan Konseling Pandohop, 2024)
The purpose of this study was to reduce students' Inferiority by giving Group Guidance services with Modeling techniques. By using quantitative and qualitative methods (Mixed Methods) and research subjects in class VII SMP Negeri 1 Ketapang, totaling 7 students. This research was conducted in two cycles. Data were collected using observation techniques, interviews and psychological scale Inferiority. The results of this study based on the results of data analysis that has been percentage obtained that inferiority in VII D class students at SMP Negeri 1 Ketapang before getting group guidance services with modeling techniques with a percentage of 80% included in the "high" category and after getting group guidance services with modeling techniques obtained a percentage of 58% in the "medium" category. It can be seen that there is a decrease after being given group guidance services with modeling techniques, meaning that inferiority in students can be reduced through group guidance services with modeling techniques.